Interaction of vascular endothelial cells with hydrophilic fullerene nanoarchitectured structures in 2D and 3D environments - Tsai-Yu Chen; Kun-Chih Cheng; Pei-Syuan Yang; Lok Kumar Shrestha; Katsuhiko Ariga; Shan-hui Hsu (Science and Technology of Advanced Materials)
The interaction between diverse nanoarchitectured fullerenes and cells is crucial for biomedical applications. Here, we detailed the preparation of hydrophilic self-assembled fullerenes by the liquid-liquid interfacial precipitation (LLIP) method and hydrophilic coating of the materials as a possible vascularization strategy. The interactions of vascular endothelial cells (ECs) with hydrophilic fullerene nanotubes (FNT-P) and hydrophilic fullerene nanowhiskers (FNW-P) were investigated. The average length and diameter of FNT-P were 16 ± 2 μm and 3.4 ± 0.4 μm (i.e. aspect ratios of 4.6), respectively. The average length and diameter of FNW-P were 65 ± 8 μm and 1.2 ± 0.2 μm (i.e. aspect ratios of 53.9), respectively. For two-dimensional (2D) culture after 7 days, the ECs remained viable and proliferated up to ~ 420% and ~ 400% with FNT-P and FNW-P of 50 μg/mL, respectively. Furthermore, an optimized chitosan-based self-healing hydrogel with a modulus of ~400 Pa was developed and used to incorporate self-assembled fullerenes as in vitro three-dimensional (3D) platforms to investigate the impact of FNT-P and FNW-P on ECs within a 3D environment. The addition of FNW-P or FNT-P (50 μg/mL) in the hydrogel system led to proliferation rates of ECs up to ~323% and ~280%, respectively, after 7 days of culture. The ECs in FNW-P hydrogel displayed an elongated shape with aligned morphology, while those in FNT-P hydrogel exhibited a rounded and clustered distribution. Vascular-related gene expressions of ECs were significantly upregulated through interactions with these fullerenes. Thus, the combined use of different nanoarchitectured self-assembled fullerenes and self-healing hydrogels may offer environmental cues influencing EC development in a 3D biomimetic microenvironment, holding promise for advancing vascularization strategy in tissue engineering.